Mathematics for physical science and engineering : symbolic computing applications in Maple and Mathematica - Harris, Frank E. (Amsterdam : Academic Press, 2014)
Mathematics for Physical Science and Engineering is a complete text in mathematics for physical science that includes the use of symbolic computation to illustrate the mathematical concepts and enable the solution of a broader range of practical problems. It enables professionals to connect their knowledge of mathematics to either or both of the symbolic languages Maple and Mathematica. Due to the increasing importance of symbolic computation, the book begins by introducing that topic, before delving into its core mathematical topics. Each of those subjects is described in principle, and then applied through symbolic computing. The aim of the text is designed to clarify and optimize the efficiency of the student's acquisition of mathematical understanding and skill and to provide students with a mathematical toolbox that will rapidly become of routine use in a scientific or engineering career.
CIP data; item not viewed.
Keywords: Maple (Computer file); Maple (Computer file); Mathematical physics -- Data processing; Engineering mathematics -- Data processing; Mathematica (Computer program language); Engineering mathematics -- Data processing; Mathematica (Computer program language); Mathematical physics -- Data processing; Mathematics; Electronic books